Report on industrial attachment with Hewlett-Packard Singapore - Seah, Suan Hee. (2008)
The report is divided into three parts: the company profile, the projects undertaken by the author were introduced and discussed (include Design and Build Manual Burn-in Tester, Set Limits for Burn-in and VSCEL Die and Improving of Low Yield Problem at TO